Nitrogen and Chemical Control Management Improve Yield and Quality in High-Density Planting of Maize by Promoting Root-Bleeding Sap and Nutrient Absorption - Liu, Xiaoming; Zhang, Liguo; Yu, Yang; Qian, Chunrong; Li, Congfeng; Wei, Shi; Li, Caifeng; Gu, Wanrong (Frontiers in Plant Science, 2022)
High planting density aggravates competition among plants and has a negative impact on plant growth and productivity. Nitrogen application and chemical control can improve plant growth and increase grain yield at high plant density. The experiment was to explore the effects of nitrogen fertilizer and plant growth regulator on maize root bleeding sap, phosphorus (P) and potassium (K) accumulation and translocation, and grain yield and quality under high plant density. Hence, we established a field study during the 2017 and 2018 growing seasons, with three nitrogen levels of N100 (100 kg ha–1), N200 (200 kg ha–1), and N300 (300 kg ha–1) at high planting density (90000 plants ha–1), and applied plant growth regulator (Yuhuangjin, the mixture of 3% DTA-6 and 27% ethephon) at the 7th leaf. Our results showed that N200 application in the combination of chemical control can regulate amino acid, mineral nutrients concentrations delivery rate in bleeding sap and improve the root bleeding sap rate. Also, the treated plant exhibits higher P and K uptake and translocation ability. Furthermore, chemical control and N200 treatment maintain a high level of ribulose-1,5-bisphosphate carboxylase (RuBPCase), phosphoenolpyruvate carboxylase (PEPCase), nitrate reductase (NR) and glutamine synthetase (GS) enzymatic activities in leaf. In addition, plant growth regulator and nitrogen application improve the enzymatic activities of GS, glutamate dehydrogenase (GDH) and glutamic-pyruvic transaminase (GPT) and contents of crude protein, lysine, sucrose and soluble sugar in grain, ultimately increase maize yield. This study suggested that N200 application combination with chemical control promoting root vitality and nutrient accumulation could improve the grain yield and quality at high plant density.